2000
DOI: 10.1074/jbc.m005832200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-I Extends in VitroReplicative Life Span of Skeletal Muscle Satellite Cells by Enhancing G1/S Cell Cycle Progression via the Activation of Phosphatidylinositol 3′-Kinase/Akt Signaling Pathway

Abstract: Interest is growing in methods toKip1 . Adenovirally mediated ectopic overexpression of p27Kip1 in exponentially growing IGF-I transgenic satellite cells reversed the increase in cyclin Ecdk2 kinase activity, pRb phosphorylation, and cyclin A protein abundance, thereby implicating an important role for p27Kip1 in promoting satellite cell senescence. These observations provide a more complete dissection of molecular events by which increased local expression of a growth factor in mature skeletal muscle fibers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 56 publications
6
161
0
2
Order By: Relevance
“…Early studies of IGF-I proliferative action performed with cultured fibroblasts (BALB/c-3T3) indicate that IGF-I acts to stimulate progression through G 1 or the G 0 /G 1 transition (Stiles et al, 1979;Clemmons et al, 1980;Wharton et al, 1981;Russell et al, 1984;Olashaw et al, 1987). More recent studies in both myocytes (Reiss et al, 1997;Chakravarthy et al, 2000) and mammary epithelial cells (Stull et al, 2002) reached the same conclusion: that is, IGF-I promotes progression through G 1 phase of the cell cycle. However, studies of estradiol-induced mitosis in the endometrium, suggest that IGF-I regulates progression through G 2 phase (Adesanya et al, 1999).…”
Section: Discussionmentioning
confidence: 49%
“…Early studies of IGF-I proliferative action performed with cultured fibroblasts (BALB/c-3T3) indicate that IGF-I acts to stimulate progression through G 1 or the G 0 /G 1 transition (Stiles et al, 1979;Clemmons et al, 1980;Wharton et al, 1981;Russell et al, 1984;Olashaw et al, 1987). More recent studies in both myocytes (Reiss et al, 1997;Chakravarthy et al, 2000) and mammary epithelial cells (Stull et al, 2002) reached the same conclusion: that is, IGF-I promotes progression through G 1 phase of the cell cycle. However, studies of estradiol-induced mitosis in the endometrium, suggest that IGF-I regulates progression through G 2 phase (Adesanya et al, 1999).…”
Section: Discussionmentioning
confidence: 49%
“…Activation of PI 3-Kinase Attenuates TRAIL Induction whereas PTEN Overexpression Induces TRAIL Expression-IGF-1, a trophic factor for intestinal mucosa (44), activates PI 3-kinase with subsequent activation of Akt/PKB in a number of cell lines (13,(45)(46)(47). To determine whether activation of PI 3-kinase can inhibit wortmannin-induced TRAIL expression, HT29 cells were pretreated with IGF-1 (50 ng/ml) for 20 min followed by treatment with wortmannin in the presence of IGF-1 (250 nM) (Fig.…”
Section: The Pi 3-kinase Inhibitor Wortmannin Induces Trail Mrna Exprmentioning
confidence: 99%
“…The pivotal role of E2F transcription factors in driving the G 1 -S transition is largely mediated by their target genes such as G 1 cyclins (18). We and others have shown that IGF-I acts on key molecular events at the G 1 /S checkpoint, leading to inactivation of RB and elevation of G 1 cyclins such as cyclin D 1 (19), E (20), and A (21). However, there is no evidence that IGF-I augments G 1 cyclin expression and RB hyperphosphorylation by up-regulating synthesis of E2F transcriptional factors.…”
mentioning
confidence: 99%